2013
DOI: 10.1016/j.cjca.2013.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and Outcome in Elderly Patients With Acute Coronary Syndrome

Abstract: The EFS is associated with increased comorbidity, longer lengths of stay, and decreased procedure use. After adjustment for burden of illness, the highest frailty category is independently associated with mortality in elderly patients with ACS. Further work is needed to determine whether the use of a validated frailty instrument would better delineate medical decision making in this important, often disadvantaged population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 30 publications
6
102
0
Order By: Relevance
“…23 In this setting frailty ranged from 10% to 48%, and higher levels of frailty were associated with worse outcomes (Table 5). 47,[49][50][51][52][53][54][55] These studies showed an independent added prognostic value of frailty assessment, and although larger studies are needed to refine risk prediction models, it is suggested that clinicians and researchers should consider how they can embed frailty measurement into clinical practice.…”
Section: Frailty In Cardiologymentioning
confidence: 99%
See 2 more Smart Citations
“…23 In this setting frailty ranged from 10% to 48%, and higher levels of frailty were associated with worse outcomes (Table 5). 47,[49][50][51][52][53][54][55] These studies showed an independent added prognostic value of frailty assessment, and although larger studies are needed to refine risk prediction models, it is suggested that clinicians and researchers should consider how they can embed frailty measurement into clinical practice.…”
Section: Frailty In Cardiologymentioning
confidence: 99%
“…The prevalence of frailty and its clinical and prognostic relevance has not as yet been well characterised in the environment of CR, although many studies have reported the measurement of frailty in patients with coronary syndromes in intensive care units or in cardiology wards, [49][50][51][52] and others have underscored the close link between frailty and CHF. [71][72][73][74][75][76][77][78][79][80] As patients after ACS or CHF represent a considerable proportion of those participating in CR, 85,86 we may suggest that frailty measurement should be performed in CR, to help plan their management and estimate their prognosis.…”
Section: Frailty and Crmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are similar to the results of a study conducted with elderly individuals of the community, in which females presented with the highest level of frailty, evaluated using the EFS, and other studies conducted in an international context with frailty evaluated based on the frailty phenotype proposed by Fried, and the proposed Frailty Index by Rockwood. (25)(26)(27) The greater prevalence of frailty in women is due to their living longer, being economically dependent, and influenced by conditions marked by sexual issues, and having a restricted social life. (28) In the present research, the prevalence of frailty can be verified in the interviewed elderly.…”
Section: Cras -Social Assistance In Referral Centersmentioning
confidence: 99%
“…The researches have also shown that fatigue and weakness in elderly patients after open heart surgery decreases physical activity and functionality level of the patients. Reduced functionality level, which is among common complications after open heart surgery, can reduce the patients' independence and increase their dependence on the family members and relatives (7).…”
Section: Introductionmentioning
confidence: 99%